WILDLIFE NECROPSY AND FORENSICS - Sriraman, P. K. ([S.l.] : CRC PRESS, 2021)
The book discusses various necropsy procedures for wild animals both for the disease investigation and forensic usage. The list of various wildlife crimes, the role of each member of wildlife crime team investigation in general and the role of pathologist in particular, (the forensic veterinary pathology)and the salient features of methodology of crime investigation is given. Information on the mistakes and omissions in forensic necropsy, negative necropsy, common errors committed by pathologist while performing forensic necropsy, postmortem appearances of common pathological conditions and estimation of age of some of the domestic animals and their foetuses is given for guidance. Various types of wounds, and the types of firearms and their terminology are also given for easy understanding about the wounds and fire arms.Note: T&F does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.
OCLC-licensed vendor bibliographic record.
Keywords: Veterinary autopsy; SCIENCE / Life Sciences / General